Climate change and zoonotic infections in the Russian Arctic - Revich, Boris (Co-Action Publishing, 2012)
Climate change in the Russian Arctic is more pronounced than in any other part of the country. Between 1955 and 2000, the annual average air temperature in the Russian North increased by 1.2°C. During the same period, the mean temperature of upper layer of permafrost increased by 3°C. Climate change in Russian Arctic increases the risks of the emergence of zoonotic infectious diseases. This review presents data on morbidity rates among people, domestic animals and wildlife in the Russian Arctic, focusing on the potential climate related emergence of such diseases as tick-borne encephalitis, tularemia, brucellosis, leptospirosis, rabies, and anthrax.